Colorectal Cancer Screening- mainstay of prevention - Namah, Manisha (Trinity Student Medical Journal, 2006)
Screening for colorectal cancer clearly reduces colorectal cancer mortality. Effective, safe, and relatively inexpensive methods for screening for the disease have been available for decades. Screening is recommended by a number of professional organizations, including the Multidisciplinary Expert Panel, the US Preventive Services Task Force and the American Cancer Society. However, no consensus has been reached on which screening modality to use. This article aims to critically assess the evidence for use of available colorectal cancer screening tests, including fecal occult blood tests, sigmoidoscopy, colonoscopy, double-contrast barium enema, and newer tests such as virtual colonoscopy and stool-based molecular screening.